Comparison of chloroquine, sulfadoxine/pyrimethamine, mefloquine and mefloquine-artesunate for the treatment of falciparum malaria in Kachin State, North Myanmar. - Smithuis, F; Shahmanesh, M; Kyaw, M; Savran, O; Lwin, S; White, N (2004)
Multi-drug resistant falciparum malaria is widespread in Asia. In Thailand, Cambodia and Vietnam the national protocols have changed largely to artesunate combined treatment regimens but elsewhere in East and South Asia chloroquine (CQ) and sulfadoxine-pyrimethamine (SP) are still widely recommended by national malaria control programmes. In Kachin State, northern Myanmar, an area of low seasonal malaria transmission, the efficacy of CQ (25 mg base/kg) and SP (1.25/25 mg/kg), the nationally recommended treatments at the time, were compared with mefloquine alone (M; 15 mg base/kg) and mefloquine combined with artesunate (MA; 15:4 mg/kg). An open randomized controlled trial enrolled 316 patients with uncomplicated Plasmodium falciparum malaria, stratified prospectively into three age-groups. Early treatment failures (ETF) occurred in 41% (32/78) of CQ treated patients and in 24% of patients treated with SP (18/75). In young children the ETF rates were 87% after CQ and 35% after SP. Four children (two CQ, two SP) developed symptoms of cerebral malaria within 3 days after treatment. By day 42, failure rates (uncorrected for reinfections) had increased to 79% for CQ and 81% for SP. ETF rates were 2.5% after treatment with M and 3.9% after treatment with MA (P > 0.2). Overall uncorrected treatment failure rates at day 42 following M and MA were 23% and 21%, respectively. Chloroquine and SP are completely ineffective for the treatment of falciparum malaria in northern Myanmar. Mefloquine treatment is much more effective, but three day combination regimens with artesunate will be needed for optimum efficacy and protection against resistance.